Estágios de Mineralização no Depósito Aurífero Pau-a-Pique, Grupo Aguapeí, Sudoeste do Estado de Mato Grosso, Brasil Central - Evidências de Química Mineral e Inclusões Fluidas - - BARBOZA, ELZIO DA SILVA; PULZ, GÊNOVA MARIA; RONCHI, LUIZ HENRIQUE; JELINEK, ANDRÉA RITTER; PINHO, FRANCISCO EGÍDIO; QUADROS, ÁLVARO PIZZATO (Pesquisas em Geociências, 2001)
The Pau-a-Pique deposit is a small gold prospect in the Southwestern of the Amazonian Craton (Mato Grosso State, Brazil). Ore types comprise quartz veins and disseminations hosted in the mylonitized metaconglomerate (Fortuna Formation, Aguapeí Group) and amphibole-biotite-chlorite mylonite. The native gold is associated with pyrite, pyrrhotite, chalcopyrite, native silver, galena, hematite, magnetite and martite. The aqueous-carbonic (type 1) and aqueous inclusions (type 2) in the quartz veins suggest that ore genesis is related to metamorphic fluids percolation during the late regional shearing. The ore remobilization was promoted by meteoric fluids, which are preserved as aqueous inclusions (type 3) in quartz veins.